Sorptive substance for recovering oil on water - produced by rendering comminuted cork oleophobic and hydrophobic by heating with steam under pressure - A, JONES J (1989)
Improved substance for the recovery of oil and similar compounds from the surface of water, and other substrates is produced from a naturally occurring arborial material, typically the cork of the cork tree (Quercus Suber.), which is subjected to a process to improve the sorptive character of the raw material, by heating under pressure for a time. Specifically, the substance is heated at 150-350 deg.C for a period of time with the application of steam at a pressure of 0-1.5 megapascals in an autoclave or similar apparatus, comminuted in size below 5 mm mesh to give a sorptive capacity for oil and related compounds of 5-10 times its own weight. ADVANTAGE-The improved material exhibits ease of collecting sorbed oil from water using a strainer of nominal mesh size to effect 100% recovery with little uptake of water. The oil and related compounds can be separated from the sorbate by the application of pressure, centrifugal force, or by solvent extraction and/or distillation.
APS
Keywords: arborial material; Cork; oil compounds; Quercus suber; sorptive capacity

Substance for recovering oil from water, etc. - esp. comprising pretreated cork - A, JONES J (1987)
A substance for recovering oil and similar cpds. from the surface of water and other substrates is claimed. The substance is cork from the cork oak (Quercus suber) which has been heated under pressure and then comminuted to less than 5mm to give a prod. with an oil sorption capacity of 5-10 times its own lot. Sorbed oil can be recovered from the cork by pressing, centrifuging, solvent extraction and/or distn., or it can be incinerated in situ or after removal from the substrate. The cork may be packaged in an oil-permeable pillow, sock or blanket. It may be used to recover oil from sand and/or shale by intimate mixing and subsequent sepn.